Carbon based electrodes in electroanalysis - Ashrafi, Amirmansoor (Univerzita Pardubice, 2014)
The thesis aims to present the performance and efficiency of various types and configurations of carbon based electrodes in electroanalysis of different kinds of analytes including heavy metals and pharmaceuticals. The thesis includes three chapters. The first chapter, theoretical part, discusses about the electroanalytical techniques, their advantages over other analytical methods, the essential components in electroanalytical techniques, the material used for construction of electrochemical electrodes and continues to state the properties and utility of various carbonaceous materials in electroanalysis. The methods, materials and instruments employed for preparing the carbon paste electrode as well as their electrochemical and physiochemical properties are explained in the final part of the first chapter. The second chapter, experimental 1, starts with an introduction about the definition of heavy metals and the importance of their determination due to their biological and environmental significance. The metallic film electrodes with a special focus on antimony film electrode are also described in the second chapter. This chapter includes five appendixes about implement of antimony film coated carbon paste electrode for determination of heavy metals. The third chapter, experimental 2, which is about the use of carbon based electrode in drug analysis starts with an introduction about the definition of drugs, their biological and environmental impact and follows by a survey about implement of carbon based electrodes in electroanalysis of drugs. The chapter in ended with two appendixes dealing with analysis of two anti-HIV drugs using carbon based electrodes.
Carbon based electrodes in electroanalysis
Keywords: uhlíkové pastové elektrody; těžké kovy; farmaceutické sloučeniny; carbon paste electrode; heavy metals; pharmaceutical compounds